2023
DOI: 10.3389/fmed.2023.1137134
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-based versus bivalirudin-based anticoagulation in pediatric extracorporeal membrane oxygenation: A systematic review

Abstract: IntroductionOptimal anticoagulation therapy is essential for the prevention of thrombotic and hemorrhagic complications in pediatric patients supported with extracorporeal membrane oxygenation (ECMO). Recent data have demonstrated bivalirudin has the potential to surpass and replace heparin as the anticoagulant of choice.MethodsWe conducted a systematic review comparing the outcomes of heparin-based versus bivalirudin-based anticoagulation in pediatric patients supported on ECMO to identify the preferred antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The GelMA hydrogel coating that contains BV was successfully produced, which acts as a direct thrombin inhibitor by binding to the anion-binding exosite of both free and clot-bound catalytic sites of thrombin. Compared with heparin, BV has better safety, reliability, and cost-effectiveness (25). Importantly, the BV-Coating GelMA hydrogel tube did not significantly affect cell growth activity nor elicit hemolysis, complement activation, or coagulation reactions when in contact with blood.…”
Section: Discussionmentioning
confidence: 99%
“…The GelMA hydrogel coating that contains BV was successfully produced, which acts as a direct thrombin inhibitor by binding to the anion-binding exosite of both free and clot-bound catalytic sites of thrombin. Compared with heparin, BV has better safety, reliability, and cost-effectiveness (25). Importantly, the BV-Coating GelMA hydrogel tube did not significantly affect cell growth activity nor elicit hemolysis, complement activation, or coagulation reactions when in contact with blood.…”
Section: Discussionmentioning
confidence: 99%
“…There are several recent review articles comparing heparin to bivalirudin for ECMO anticoagulation (48)(49)(50)(51)(52)(53)(54)(55), and all of them favor bivalirudin (Table 8). It should be noted, however, that all but one of these studies are meta-analyses and are compromised by the lack of standard definitions for bleeding and thrombosis.…”
Section: Recently Published Review Articlesmentioning
confidence: 99%
“…Nevertheless, even though bivalirudin can be considered a good alternative to heparin, its superiority has not been showed so far. Based on these considerations, Valdes CA et al, 29 performed a systematic review to evaluate the outcomes of heparin-based versus bivalirudin-based anticoagulation during neonatal an pediatric ECMO. The authors showed that patients anticoagulated with bivalirudin had a lower rate of bleeding, transfusions and thrombotic complications.…”
mentioning
confidence: 99%